Optimizing Multimodal Transportation and the Role of Freight Forwarding in the Palm Oil (CPO) Supply Chain in Indonesia - Nur Fauzi, Muhammad; Tohir, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This study aims to analyze the role of multimodal transportation and freight forwarding in optimizing the Crude Palm Oil (CPO) supply chain in Indonesia, including logistical challenges, transportation mode efficiency, and the impact of digital technology and government regulations. Employing a descriptive qualitative method with a systematic literature review, the research findings indicate that multimodal transportation and freight forwarding are crucial for logistics cost efficiency, despite facing implementation hurdles such as fragmentation and manual processes. The upstream CPO supply chain is fragmented with inadequate infrastructure, yet shorter distribution patterns and company-managed transportation prove more efficient. Technologies like the Internet of Things (IoT) and blockchain hold significant potential to enhance transparency and efficiency. In conclusion, optimizing the CPO supply chain necessitates infrastructure investment, farmer empowerment, regulatory refinement, and widespread adoption of digital technologies to achieve Indonesia's Logistics Vision 2025.